Homogeneous Polyporus Polysaccharide Inhibit Bladder Cancer by Resetting Tumor-Associated Macrophages Toward M1 Through NF-κB/NLRP3 Signaling - Liu, Chunping; He, Dongyue; Zhang, Shihui; Chen, Huiqi; Zhao, Jie; Li, Xiong; Zeng, Xing (Frontiers in immunology, 2022)
Bladder cancer(BC)is one of the most common urinary system tumors, which characterized by a high incidence. Polyporus polysaccharide is the main active component of polyporus, which is clinically used in the treatment of bladder cancer, but the mechanism is not clear. In previous study, we isolated homogeneous polyporus polysaccharide(HPP) with high purity from polyporus. The goal of this study was to assess the polarization of macrophages induced by HPP in the bladder tumor microenvironment and explored its anti-bladder cancer mechanism through BBN bladder cancer rat model and Tumor associated macrophages(TAM). The results suggested that HPP regulates TAM polarization to improve the tumor inflammatory microenvironment, possibly through the NF-κB/NLRP3 signaling pathway. Our results suggested that HPP may be a potential therapeutic agent for bladder tumors.